Proposition of diagnostic tool to provide indicatives about the understanding of biological knowledge and their interrelationships - Andrade Caldeira, Ana Maria de [UNESP]; Siebert, Paloma Rodrigues; Correa, Andre Luis; Meglhioratti, Fernanda Aparecida; Brando, Fernanda da Rocha; Maricato, Fulvia Eloa; Della Justina, Lourdes Aparecida; Bologna Soares de Andrade, Mariana Aparecida; Oliveira, Thais Benetti de [UNESP]; Silva Augusto, Thais Gimenez da [UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2016)
This paper describes the developing and validating steps of a Likert's evaluative scale. The aim is to systematize the answers of Biological Sciences students about to: 1) Understanding or not understanding the scientific knowledge; and 2) If there is a relationship among scientific concepts in order to contemplate a systemic thinking about natural phenomena. The described scale was validated by Cronbach's Alpha tests (alpha = 0.741), KMO (0.779) and Bartlett (0.000) and a Multivariate Analysis was fulfilled, type Principal Component Analysis (PCA). We understood this kind of instrument allows a large amount of data to be collected and it groups can be compared efficiently, which justified the development of evaluative scale presented here.
Keywords: biology education; evaluative scale; likert; systemic knowledge; fragmented knowledge